The Effect of Gender and Usage of Social Networking Sites on Narcissism - Afentouli Panagiota; Poulitsas Nikolaos (2015)
Introduction, Narcissism Definition, Narcissism and Gender, Social Networking Sites, Facebook and Narcissism, Facebook and Twitter and Narcissism, Rationale, Hypotheses, Method, Design, Participants, Materials, Procedure, Ethics, Analytic Strategy, Results, Descriptive Statistics, Results Description, Discussion, Summarized Results, Previous Research, Strengths, Limitations, Conclusion and Further Research, References, Appendices, Briefing, Consent Form, Debriefing, Narcissistic Personality Inventory - 16, Statistical Analysis, Personal Development Planning.